The dynamics of wage dispersion between firms: The role of firm entry and exit - Benedikt Schröpf (Journal for Labour Market Research, 2023)
Although wage inequality is an important and widely studied issue, the literature is vastly silent on the relationship between firm entry and exit and the wage dispersion between firms. Using a 50% random administrative sample of West German establishments over the period 1976-2017, I study wage dispersion dynamics between and within the groups of entering, exiting, and incumbent establishments by examining the distribution of average wages across establishments. The results show that entering establishments became increasingly unequal over time, thereby contributing to the rise in wage dispersion between establishments. However, exit rates of young and low-wage establishments have dampened this effect. These findings suggest considering the consequences for wage inequality when designing and assessing policy instruments for firm entry and exit.
Keywords: L26; M13; J31; 330; Firm entry; Firm exit; Wage dispersion; Firm dynamics; Germany